Ativos intangíveis e a relevância da informação contábil para o mercado de capitais em empresas brasileiras - Amanda de Carvalho Taroco Tavares (2019)
In financial literature, accounting information is relevant from the moment it presents a predictive association with the market value of organizations according to Barth, Beaver and Landsman (2001). Thus, the purpose of this research was to analyze the influence of intangible assets on the relevance of accounting information of Brazilian companies listed in B3. The research describes the relationship between intangible assets and market value, the data used were obtained from the financial statements and those analyzed through panel data regression, an adaptation of the Feltham and Ohlson (1995) model. . For the research, two periods were considered for the market value variable, first and second quarter of the date of disclosure of the financial statements, that is, March 31 and June 30 with a tolerance of 5 days. The study sample consisted of 156 and 154 companies listed in B3 from 2011 to 2017 for the first and second period respectively. The results allowed us to identify the positive influence of identifiable and non-identifiable intangible assets, goodwill, on the relevance of accounting information. Both identifiable assets and goodwill are relevant to the Brazilian capital market, ie, they positively influence the value of companies from the investors' point of view. Therefore, the research demonstrates the importance of disclosing intangible assets, as they add market value to companies.